K BUDAYA PENGGEMAR K-POP DAN KEHIDUPAN SOSIAL REMAJA DI KOTA DENPASAR DALAM MEMPERTAHANKAN EKSISTENSINYA: BUDAYA PENGGEMAR K-POP DAN KEHIDUPAN SOSIAL REMAJA DI KOTA DENPASAR DALAM MEMPERTAHANKAN EKSISTENSINYA - I Wayan Dikse Pancane (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2022)
Groups and communities are born based on motivation and similarity of identity to interact for a common purpose or will. The inclusion of K-pop also made its fans categorize themselves in a fanbase. However, the community finds it difficult for its members who are worried about not having friends at the event. Causing enthusiasm to decrease and affect the existence of Carat Bali. This research is qualitative research with a type of phenomenological descriptive research. The validity of this research data was obtained from engineering triangulation and source triangulation. Based on research that has been done, the communication patterns used by the Carat Bali Community are primary communication patterns, secondary